2018
DOI: 10.1093/annonc/mdy414
|View full text |Cite
|
Sign up to set email alerts
|

Nine weeks versus 1 year adjuvant trastuzumab in combination with chemotherapy: final results of the phase III randomized Short-HER study

Abstract: This study failed to show the non-inferiority of a shorter trastuzumab administration. 1-year trastuzumab remains the standard. However, a 9-week administration decreases the risk of severe cardiac toxicity and can be an option for patients with cardiac events during treatment and for those with a low risk of relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 21 publications
(23 reference statements)
1
117
0
2
Order By: Relevance
“…Some support for a shorter treatment duration was provided by a small trial, in which 9 weeks of trastuzumab showed a benefit similar to that from 1 year of trastuzumab when given with standard chemotherapy . Several other trials failed to show noninferiority of the shorter trastuzumab duration (9 weeks or 6 months) …”
Section: Optimizing Schedules For Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Some support for a shorter treatment duration was provided by a small trial, in which 9 weeks of trastuzumab showed a benefit similar to that from 1 year of trastuzumab when given with standard chemotherapy . Several other trials failed to show noninferiority of the shorter trastuzumab duration (9 weeks or 6 months) …”
Section: Optimizing Schedules For Cancer Therapymentioning
confidence: 99%
“…64,65 Several other trials failed to show noninferiority of the shorter trastuzumab duration (9 weeks or 6 months). [66][67][68] The larger, phase 3 PHARE (Protocol for Herceptin as Adjuvant Therapy With Reduced Exposure) and PERSEPHONE (6 versus 12 months of adjuvant trastuzumab for HER2-positive early breast cancer) trials in HER2-positive, early breast cancer had similar designs and assessed the same clinical endpoints. 69,70 The final PHARE analysis, with a median follow-up of 7.5 years, failed to show that 6 months of trastuzumab was noninferior to 12 months of trastuzumab; the frequency of cardiac events was lower in the 6-month arm.…”
Section: Area Generic Biosimilarmentioning
confidence: 99%
“…Trastuzumab (Herceptin), a monoclonal antibody against subdomain IV of the HER2extracellular domain (ECD), combined with chemotherapy can significantly improve the prognosis of HER2-positive BC patients compared with chemotherapy alone, which has been demonstrated in the Cochrane meta-analyses [7,8]. Furthermore, according to several large and long-term followup trials, one year of trastuzumab therapy plus chemotherapy has become the standard of care for HER2-positive early breast cancer (EBC) patients [9][10][11][12]. However, cases of drug resistance remain and about 30% of patients relapse after trastuzumab therapy and new approaches are required [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, multiple trials, including two phase 3 randomised trials, 7,8 one three-group phase 2 trial, 2 and two single-group phase 2 trials, 9,10 have found an excellent therapeutic index associated with novel, anthracycline-free regimens. Additionally, five studies [11][12][13][14][15][16] evaluated whether a shorter duration of trastuzumab is non-inferior to the standard year. Non-inferiority could not be concluded in the first four studies; [11][12][13][14] thus, the debate appeared to be closed.…”
Section: Is the Duration Of Adjuvant Trastuzumab Debate Still Clinicamentioning
confidence: 99%